Pengembangan Kewirausahaan Untuk Meningkatkan Kesejahteraan Petani di Desa Minasabaji Kecamatan Bantimurung Kabupaten Maros - Irfan, Andi; Pasulu, Milka; Ansar, Ansar; Ismail, Azhary (Penerbit Widina, Widina Media Utama, 2025)
The purpose of this community service activity is to develop entrepreneurship among farmers in Minasabaji Village, Bantimurung District, Maros Regency in order to improve their welfare. Limited market access, entrepreneurial knowledge, and low selling value of agricultural products are often obstacles for village farmers to increase their income. In this activity, a series of entrepreneurship training, business management assistance, and marketing network development were carried out. Through this program, village farmers are expected to be able to maximize the potential of local resources to create value-added products that are competitive in the market. The results of the community service show that developing entrepreneurship can increase farmers' income, strengthen village economic resilience, and open up new job opportunities in the agricultural sector.ABSTRAKTujuan dari kegiatan pengabdian masyarakat ini adalah untuk mengembangkan kewirausahaan di kalangan petani di Desa Minasabaji Kecamatan Bantimurung Kabupaten Maros guna meningkatkan kesejahteraan mereka. Keterbatasan akses pasar, pengetahuan kewirausahaan, dan rendahnya nilai jual produk pertanian seringkali menjadi kendala bagi petani desa untuk meningkatkan pendapatan mereka. Dalam kegiatan ini, dilakukan serangkaian pelatihan kewirausahaan, pendampingan manajemen usaha, serta pengembangan jaringan pemasaran. Melalui program ini, petani desa diharapkan mampu memaksimalkan potensi sumber daya lokal untuk menciptakan produk bernilai tambah yang memiliki daya saing di pasar. Hasil pengabdian menunjukkan bahwa pengembangan kewirausahaan mampu meningkatkan pendapatan petani, memperkuat ketahanan ekonomi desa, serta membuka peluang kerja baru di sektor pertanian.